EVALUASI KEBIJAKAN PELAKSANAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN DI KABUPATEN HALMAHERA TENGAH - Laher Ali; A. Masrich (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2017)
The authors are interested in taking the title Evaluation of Policy Implementation of the Integrated Administrative Service District in Central Halmahera, North Maluku. This study aims to determine how the policy evaluation and implementation PATEN enabling and inhibiting factors PATEN policy implementation. The location of this research is in the district of South Weda Central Halmahera in North Maluku province. This study uses the theory Waynes Parson in Palumbo and the size of the policy evaluation is based on the theory that the evaluation process, the evaluation of formative and summative evaluation. policy resources, communication among organizations, characteristic of the implementing agencies, economic, social and political conditions and the tendencies of implementation. This research uses descriptive method with qualitative approach. Data collection techniques are interviews, document analysis and observation. The data obtained were processed with qualitative data analysis. Informants in this study were 1) the Regent of Halmahera, 2) Regional Secretary, 3) Assistant for Public Administration, Law and Authority, 4) Head of Governance Regional Secretariat of Central Halmahera, 5) Head of Integrated Licensing Service Agency, 6) Head Weda South 7) The community served Based on the research results we concluded that the implementation of the PATEN in the district of South Central Halmahera Weda considered not running optimally. This is due not been reflected in the elaboration of management commitment to the programs and activities of the OPD related, yet the drafting SOP to realize the translation of the vision - the mission of the organization, there are no guidelines for minimum service standards, unclear tasks and functions of the technical team so that the conduct of licensing has not been fully included effective, institutional structure did not reflect the needs and interests of improving the service function to society, Inkonsisiten and lack of support of stakeholders in the implementation of technical policy administration services licensing, not optimal formulation of technical policy administration services licensing, weak coordination between leaders and subordinates in the implementation of integrated license service with the technical team in its OPD and has not implemented the promotion and development of quality apparatus BPPT, facilities and infrastructure not meet minimum service standards have not yet optimal application of ICT-based information system